2018
DOI: 10.1038/s41467-017-02746-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of SQSTM1/p62 mediates the link between redox state and protein homeostasis

Abstract: Cellular homoeostatic pathways such as macroautophagy (hereinafter autophagy) are regulated by basic mechanisms that are conserved throughout the eukaryotic kingdom. However, it remains poorly understood how these mechanisms further evolved in higher organisms. Here we describe a modification in the autophagy pathway in vertebrates, which promotes its activity in response to oxidative stress. We have identified two oxidation-sensitive cysteine residues in a prototypic autophagy receptor SQSTM1/p62, which allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
156
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(161 citation statements)
references
References 59 publications
4
156
1
Order By: Relevance
“…Mammalian cells: Immunoblotting on cells was performed as described previously 42 . In brief, cells were lysed on ice in RIPA buffer (Sigma) supplemented with 1x Halt TM protease and phosphatase inhibitor cocktail (Thermo Scientific).…”
Section: Immunoblot Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Mammalian cells: Immunoblotting on cells was performed as described previously 42 . In brief, cells were lysed on ice in RIPA buffer (Sigma) supplemented with 1x Halt TM protease and phosphatase inhibitor cocktail (Thermo Scientific).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…Insoluble material was removed by centrifugation and the supernatant was subjected to SDS-PAGE analysis. D. melanogaster: Fly sample preparation and immunoblotting were performed as described previously 42 . Briefly, 20 flies per group were homogenized on ice in a specialised buffer (1.5% Triton X-100 (Promega), complete mini EDTA-free proteinase inhibitor (Sigma), PBS 1X).…”
Section: Immunoblot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy is an evolutionarily conserved degradation system of defective proteins and subcellular structures, and an early event in autophagy induction is the nuclear translocation and transactivation of the basic Helix-Loop-Helix transcription factor HLH-30 39,38 . Oxidative stress is one of the various conditions that activate autophagy (reviewed in 64,65 ) and several components of the autophagy machinery are redox regulated by ROS-mediated mechanisms in different organisms 66,67,68 . Using a HyPer fluorescent biosensor 69 we found that gsr-1(m+,z-) worms have wild type levels of H2O2 (A. Miranda-Vizuete, unpublished results), suggesting that they are not under oxidative stress and consistent with the lack of HLH-30::GFP nuclear translocation or increased SQST-1:GFP foci in these animals.…”
Section: Glutathione-dependent Regulation Of Autophagymentioning
confidence: 99%